DOI: 10.11606/d.22.2004.tde-23062005-084422
|View full text |Cite
|
Sign up to set email alerts
|

"Qualidade de vida e qualidade de vida no trabalho de profissionais de enfermagem atuantes em unidades do bloco cirúrgico"

Abstract: À minha família que torceu e compartilhou comigo em todas as etapas da realização deste estudo. A todos os profissionais de enfermagem que participaram desta pesquisa, meus sinceros agradecimentos. Aos hospitais envolvidos neste estudo, por permitirem a realização da coleta de dados. Ao Prof. Dr. Vanderlei José Hass pela disponibilidade em avaliar e auxiliar em todas as etapas de elaboração da pesquisa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2
33

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(57 citation statements)
references
References 28 publications
3
19
2
33
Order By: Relevance
“…This way, the employed QLW concept was sometimes associated to the satisfaction with some work components (32,35,(38)(39) , like payment, autonomy, professional status, and others; and at other times, it was associates to the worker's largest participation inside the organization (26) , corroborating with other authors who state that Brazilian studies adopt the QLW thematic under distinct focuses (36,41) . Four studies used the term QLW, three of which presented the definition that would be used in the study (26,36,39) . The term satisfaction at work was employed in 13 studies, but only five (27,30,32,35,38) presented the applied concept.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…This way, the employed QLW concept was sometimes associated to the satisfaction with some work components (32,35,(38)(39) , like payment, autonomy, professional status, and others; and at other times, it was associates to the worker's largest participation inside the organization (26) , corroborating with other authors who state that Brazilian studies adopt the QLW thematic under distinct focuses (36,41) . Four studies used the term QLW, three of which presented the definition that would be used in the study (26,36,39) . The term satisfaction at work was employed in 13 studies, but only five (27,30,32,35,38) presented the applied concept.…”
Section: Resultssupporting
confidence: 74%
“…The term satisfaction at work was employed in 13 studies, but only five (27,30,32,35,38) presented the applied concept. It was observed that, in the full-text dissertations and theses (26)(27)32,35,36,(38)(39) , the authors presented the adopted concepts. The same did not occur in the articles, in which most authors were not concerned with presenting the definition that would be used in the study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations